TASAWUF DI INDONESIA: SEJARAH PERKEMBANGAN DAN TOKOH- TOKOHNYA - Muhamad Ghifari; Khairi Ananda Jasofi; Maftuh Ajmain (CV. Adiba Aisha Amira, 2025)
Sufism is a science that studies spirituality and mysticism in Islam. Sufism focuses on developing spirituality and self-awareness through spiritual practice, meditation, and the practice of Islamic teachings. In Indonesia, Sufism has a long, rich and complex history of development. Since the arrival of Islam to the archipelago in the 13th century, Sufism has become an integral and essential part of the spiritual life of the Indonesian Muslim community. Through the influence of ulama, Sufis and intellectuals from the Middle East, Southeast Asia and others, Sufism in Indonesia has developed into a unique, distinctive and diverse spiritual tradition. This process has shaped the spiritual identity of the Indonesian Muslim community and enriched their spiritual life